Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x*4/5:2=6/7
x*4/5=6/7*2
x*4/5=12/7
x=12/7:4/5
x=15/7
6/5:x:5/4=10/15
6/5:x=10/15*5/4
6/5:x=5/6
x=6/5:5/6
x=36/25
khỏi chép đề nha
a\Câu 1:
200 : ( 15 - x ) = 15 + 5
200 : ( 15 - x ) = 20
15 - x = 200 : 20
15 - x = 10
x = 15 - 10
x = 5
Câu 2:
63 : ( x - 5 ) = 22 -1
63 : ( x - 5 ) = 21
x - 5 = 63 : 21
x - 5 = 3
x = 3 + 5
x = 8
3 x 15 + 21 x 15 + 85 x 5
= 45 + 315 + 425
= 785
15 - 30 + 40
= 25
21 + 19 - 50 + 10
= 0
\(\dfrac{1}{5}-\dfrac{1}{4}+2\)
\(=-\dfrac{1}{20}+2\)
\(=\dfrac{39}{20}\)
\(\left(\dfrac{1}{4}+\dfrac{1}{6}\right)\times\left(\dfrac{1}{2}-\dfrac{1}{4}\right)\)
\(=\dfrac{5}{12}\times\dfrac{1}{4}\)
\(=\dfrac{5}{12}\times\dfrac{3}{12}\)
\(=\dfrac{5}{48}\)
\(\dfrac{1}{10}+\dfrac{1}{5}-\dfrac{3}{4}\)
\(=-\dfrac{9}{20}\)
\(3\times15+21\times15+85\times5\\ =15\times\left(3+21\right)+425\\ =15\times24+425\\ =360+425\\ =785\)
\(15-30+40\\ =\left(15+40\right)-30\\ =55-30\\ =25\)
\(21+19-50+10\\ =\left(21+19\right)-\left(50-10\right)\\ =40-40\\ =0\)
\(\dfrac{1}{5}-\dfrac{1}{4}+2\)
\(=\dfrac{4}{20}-\dfrac{5}{20}+\dfrac{40}{20}\)
\(=\dfrac{\left(4+40\right)}{20}-\dfrac{5}{20}\)
\(=\dfrac{44}{20}-\dfrac{5}{20}\)
\(=\dfrac{39}{20}\)
\(\left(\dfrac{1}{4}+\dfrac{1}{6}\right)\times\left(\dfrac{1}{2}-\dfrac{1}{4}\right)\)
\(=\dfrac{5}{12}\times\dfrac{1}{4}\)
\(=\dfrac{5}{48}\)
\(\dfrac{1}{10}+\dfrac{1}{5}-\dfrac{3}{4}\)
\(=\dfrac{2}{20}+\dfrac{4}{20}-\dfrac{15}{20}\)
\(=\dfrac{6}{20}-\dfrac{15}{20}\)
\(=-\dfrac{9}{20}\)
`#3107.101107`
a)
\(x\times\dfrac{4}{5}\div2=\dfrac{6}{7}\\x\times\dfrac{2}{5}=\dfrac{6}{7}\\ x=\dfrac{6}{7}\div\dfrac{2}{5}\\ x=\dfrac{15}{7} \)
Vậy, \(x=\dfrac{15}{7}\)
b)
\(\dfrac{6}{5}\div x\div\dfrac{5}{4}=\dfrac{10}{15}\\ \dfrac{24}{25}\div x=\dfrac{10}{15}\\ x=\dfrac{24}{15}\div\dfrac{10}{15}\\ x=\dfrac{36}{25}\)
Vậy, \(x=\dfrac{36}{25}.\)
a)x*4/5:2=6/7 b)6/5:x:5/4=10/15
x*4/5=6/7 x 2 6/5:x=10/15 x 5/4
x*4/5=12/7 6/5:x=5/6
x=12/7:4/5 x=6/5:5/6
x=15/7 x=36/25
a) x * 4/5 : 2 = 6/7
x * 4/5 = 6/7 *2
x *4/5 = 12/7
x = 12/7 : 4/5
x = 15/7
Vậy x = 15/7
`x xx4/5 :2=6/7`
`x xx 4/5xx1/2=6/7`
`x xx2/5=6/7`
`x=6/7:2/5`
`x=6/7xx5/2`
`x=15/7`
b)
`6/5:x:5/4=10/15`
`6/5:x xx4/5=2/3`
`6/5:x=2/3:4/5`
`6/5:x=2/3xx5/4`
`6/5:x=5/6`
`x=6/5:5/6`
`x=6/5xx6/5`
`x=36/25`
a) x × 4/5 : 2 = 6/7
x × 4/5 = 6/7 × 2
x × 4/5 = 12/7
x = 12/7 : 4/5
x = 15/7
b) 6/5 : x : 5/4 = 10/15
6/5 : x : 5/4 = 2/3
6/5 : x = 2/3 × 5/4
6/5 : x = 5/6
x = 6/5 : 5/6
x = 36/25